STUDI HASILBUDIDAYA SECARA EKSITU BEBERAPA JENIS TUMBUHAN OBAT SEBAGAI PERTIMBANGAN KONSEP PENGEMBANGAN AGROFORESTRI BERBASIS TUMBUHAN OBAT - Siti Hamidah; Yudi Firmanul Arifin; Adistina Fitriani (Jurnal Hutan Tropis, 2020)
. Herbal medicines are very potential, because Indonesia is known as the second largest megabiodiversity after Brazil, especially since the current world medical trend applies the concept of "back to nature". Plants are a source of biological chemicals, so biodiversity is considered as a chemical industry or factory producing throughout the year. Research of local wisdom for ulilizing medical plants in South Kalimantan has been done. The results showed that there are many kinds of medicinal plants originating from the forest, but their exploitation has not been accompanied by cultivation. This is very unfortunate considering that there has not been a serious effort in cultivation, it is feared that it will make medicinal plants increasingly difficult to obtain, especially based on research results of 80% of medicinal plants that are utilized are the stem and roots.It is necessary to conduct research on the results of cultivation of medicinal plants outside their habitat. The study was conducted on 6 (six) kind of medicinal plants which are widely used by the “batra” in South Kalimantan, but availability in nature has begun to be difficult to find. Cultivation is done outside the habitat (exitu) by cuttings and saplings, and after 4 (four) months the growth response is observed. The results showed that kayu sisil laki (Litsea sp) and manggarsih (Parameria laevigata (Juss) Moldenke) are the most potential to be developed in critical lands (marginal), can live in open land, including in lands where agroforestry cultivation develops because it has the best growth response.